2019
DOI: 10.1177/1369433219850091
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation on ultimate load-carrying capacity of concrete-filled steel tubular arch structure with preload

Abstract: When casting wet concrete into hollow steel tubular arch during the construction process of a concrete-filled steel tubular arch bridge, an initial stress (due to dead load, etc.) would be produced in the steel tube. In order to understand the influence of this initial stress on the strength of the concrete-filled steel tubular arch bridge, a total of four single tubular arch rib (bare steel first) specimens (concrete-filled steel tubular last) with various initial stress levels were constructed and tested to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Thus, it was usually considered as one of the parameters for the structural optimization of buried arch culverts. Through the numerical simulation of different rise-span ratio, Huang et al (2019) examined the ultimate bearing capacity of the concrete-filled steel tube arch. The study found the reduction factor of concrete-filled steel tubular arch structure was positively related to the rise-span ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it was usually considered as one of the parameters for the structural optimization of buried arch culverts. Through the numerical simulation of different rise-span ratio, Huang et al (2019) examined the ultimate bearing capacity of the concrete-filled steel tube arch. The study found the reduction factor of concrete-filled steel tubular arch structure was positively related to the rise-span ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Concrete-filled steel tubes have good mechanical properties by optimizing the material properties of both steel and concrete [1]. And they have been widely used in recent decades, especially in arch bridges [2,3].…”
Section: Introductionmentioning
confidence: 99%